Charge‐Assisted Ionic Hydrogen‐Bonded Organic Frameworks: Designable and Stabilized Multifunctional Materials - Chen, Xu‐Yong; Cao, Li‐Hui; Bai, Xiang‐Tian; Cao, Xiao‐Jie (Chemistry : a European journal, 2024)
Hydrogen‐bonded organic frameworks (HOFs) are a class of crystalline framework materials assembled by hydrogen bonds. HOFs have the advantages of high crystallinity, mild reaction conditions, good solution processability, and reproducibility. Coupled with the reversibility and flexibility of hydrogen bonds, HOFs can be assembled into a wide diversity of crystalline structures. Since the bonding energy of hydrogen bonds is lower than that of ligand and covalent bonds, the framework of HOFs is prone to collapse after desolventisation and the stability is not high, which limits the development and application of HOFs. In recent years, numerous stable and functional HOFs have been developed by π–π stacking, highly interpenetrated networks, charge‐assisted, ligand‐bond‐assisted, molecular weaving, and covalent cross‐linking. Charge‐assisted ionic HOFs introduce electrostatic attraction into HOFs to improve stability while enriching structural diversity and functionality. In this paper, we review the development, the principles of rational design and assembly of charge‐assisted ionic HOFs, and introduces the different building block construction modes of charge‐assisted ionic HOFs. Highlight the applications of charge‐assisted ionic HOFs in gas adsorption and separation, proton conduction, biological applications, etc., and prospects for the diverse design of charge‐assisted ionic HOFs structures and multifunctional applications. Strategies for the construction of charge‐assisted ionic hydrogen‐bonded organic frameworks (HOFs) as well as recent advances form the focus of this review. The applications of these charge‐assisted ionic hydrogen‐bonded organic frameworks in gas adsorption and separation, proton conduction, and biological applications are highlighted, as well as prospects for future developments in this field.